Dynactin suppresses the retrograde movement of apically localized mRNA in Drosophila blastoderm embryos. - Vendra, G; Hamilton, R; Davis, I (2007)
Motor dependent transport of mRNA is a key mechanism in axis specification during development. Apical transport and anchoring of wingless and pair-rule transcripts in the Drosophila syncytial blastoderm embryo is mediated by cytoplasmic Dynein, the major minus end directed microtubule dependent molecular motor. Here, we show that, despite apical transport of mRNA being highly directional, mRNA particles often pause and move backward toward the plus ends of microtubules. We suggest that this retrograde movement helps overcome cellular obstructions. We show that the plus end movement of apical mRNA is independent of the major plus end microtubule motors Kinesin-1 and Kinesin-2. In contrast, Dynactin, a Dynein processivity factor, is required to suppress retrograde mRNA movements, as well as for efficient minus end motility. We propose that Dynein itself, rather than the activity of a plus end motor, is responsible for the plus end movements of the mRNA and that Dynactin is involved in preventing short reverse movements of the Dynein motor, known to occur in vitro.